THE INFLUENCE OF BRAND EXPERIENCE AND BRAND IMAGE ON ELECTRONIC WORD OF MOUTH FOR LOCAL FASHION BRANDS: A STUDY OF GENERATION Z CONSUMERS - Khairu Nisa Salsabila Putri; Febzi Fiona (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study examines the psychological mechanism through which brand experience and brand image influence e-WOM among Generation Z consumers of Jiniso, emphasizing brand love as an emotional mediator that addresses existing research gaps. Research Methodology: This study employed a quantitative cross-sectional survey design involving 260 Generation Z consumers of the local fashion brand Jiniso in Bengkulu City, Indonesia. Data were collected through online questionnaires using a five-point Likert scale. Respondents were selected via non-probability snowball sampling due to the absence of a sampling frame. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Results: The findings demonstrate that brand experience and brand image significantly enhance brand love, which subsequently drives e-WOM. Brand love partially mediates the relationship between brand experience and e-WOM and fully mediates the effect of brand image on e-WOM. These results emphasize that emotional attachment plays a crucial role in transforming consumer perceptions and experiences into active brand advocacy. Conclusions: Brand love mediates the relationship between brand experience, brand image, and e-WOM, particularly for brand image, whose influence occurs primarily through emotional attachment. However, findings are limited to Jiniso consumers and should not be generalized. Limitations: This study is limited by its reliance on closed-ended questionnaires and focus on Generation Z consumers of a single brand. Future research should examine additional e-WOM antecedents, including customer satisfaction, brand engagement, and social influence. Contributions: This study highlights brand love as an emotional mechanism linking brand evaluations to e-WOM among Generation Z and recommends that local fashion brands emphasize emotional attachment to strengthen consumer advocacy..